Exposure to ambient particulate matter and hyperuricemia: An eight-year prospective cohort study on male traffic officers in China - Yong-Xiang Tang; Yun-Ting Zhang; Yu-Jie Xu; Zhengmin (Min) Qian; Michael G. Vaughn; Stephen Edward McMillin; Gong-Bo Chen; Hui-Dong Song; Ying-Jun Lu; Yan-Ru Li; Guang-Hui Dong; Zhi Wang (Ecotoxicology and Environmental Safety, 2023)
Background and objectives: Studies on the effects of airborne particulates of diameter ≤ 1 µm (PM1), airborne particulates of diameter ≤ 2.5 µm (PM2.5) and airborne particulates of diameter ranges from 1 to 2.5 µm (PM1–2.5) on incidence of hyperuricemia are limited. We aimed to investigate the associations between PM1, PM2.5, and PM1–2.5 and hyperuricemia among male traffic officers. Methods: We conducted a prospective cohort study of 1460 traffic officers without hyperuricemia in Guangzhou, China from 2009 to 2016. Exposures of PM1 and PM2.5 were estimated with a spatiotemporal model. PM1–2.5 concentrations were calculated by subtracting PM1 from PM2.5 concentrations. Cox's proportional hazards regressions models were used to examine the association between PM1, PM2.5, and PM1–2.5 and hyperuricemia, adjusted for potential confounders. Associations between PM1, PM2.5, and PM1–2.5 and serum uric acid (SUA) levels were evaluated with multiple linear regression models. Results: Hazard ratios (HRs) and 95% confidence intervals (CIs) of hyperuricemia associated with 10 μg/m3 increment in PM1, PM2.5, and PM1–2.5 were 1.67 (95% CI:1.30–2.36), 1.49 (95% CI: 1.27–1.75), and 2.18 (95% CI: 1.58–3.02), respectively. The SUA concentrations increased by 12.23 μmol/L (95% CI: 5.91–18.56), 6.93 μmol/L (95% CI: 3.02–10.84), and 8.72 μmol/L (95% CI: 0.76–16.68) per 10 μg/m3 increase in PM1, PM2.5, and PM1–2.5, respectively. Stratified analyses indicated the positive associations of PM2.5 and PM1–2.5 with SUA levels were stronger in non-smokers, and PM1, PM2.5, and PM1–2.5 with SUA levels were stronger in non-drinkers. Conclusion: Long-term PM1, PM2.5, and PM1–2.5 exposures may increase the risk of hyperuricemia and elevate SUA levels among male traffic officers, especially in non-smokers and non-drinkers.